Factors Affecting Marketing Performance at Erlangga Publisher, Semarang Branch - Hermanto, Hermanto; Prasetyo, Ahmad Fajar; Djastuti, Indi (Economic and Business Horizon, 2025)
The purpose of this study is to test the inconsistency of research findings from previous studies regarding what aspects influence salesperson performance. This study also used a quantitative approach by involving 67 respondents, namely the sales force of PT Erlangga Semarang Branch using a questionnaire. This questionnaire was then analyzed using the Partial Least Square technique with the help of SmartPLS software. The results of this study show that the performance of market personnel is not influenced by transformational or transactional leadership styles. Rather, both leadership styles will affect marketers' performance if job satisfaction becomes the mediator between them. This study also proves that job satisfaction also affects the performance of marketers at PT Erlangga Semarang Branch. This result certainly provides new insights for PT Erlangga Cabang Semarang and other companies that understanding employee job satisfaction is one of the factors so that leadership style and performance are connected.